Combined dehydrogenation of glycerol with catalytic transfer hydrogenation of H2 acceptors to chemicals: Opportunities and challenges - Zhang, Guangyu; Zhao, Jian; Jin, Xin; Qian, Yanan; Zhou, Mingchuan; Jia, Xuewu; Sun, Feng; Jiang, Jie; Xu, Wei; Sun, Bing (Frontiers in Chemistry, 2022)
Catalytic transformation of low-cost glycerol to value-added lactic acid (LA) is considered as one of the most promising technologies for upgrade of glycerol into renewable products. Currently researches reveal that anaerobic transformation of glycerol to LA could also obtain green H2 with a same yield of LA. However, the combined value-added utilization of released H2 with high selectivity of LA during glycerol conversion under mild conditions still remains a grand challenge. In this perspective, we present current strategies for combined dehydrogenation and catalytic transfer hydrogenation between glycerol and H2 acceptors （such as CO2） to LA and other chemicals. The aim of this overview is to provide a general guidance on atomic economic reaction pathway for upgrade low-cost glycerol to LA.